Generalized Green's matrix for linear pulse boundary-value problems - Karandjulov, L.I. (Український математичний журнал, 1994)
An algebraic criterion of solvability and the structure of a general solution are found for a linear boundary-value problem for systems of differential equations with pulse effects. The generalized Green's matrix is constructed. Одержано алгебраїчний критерій розв'язності та структуру загального розв'язку крайової задачі для системи диференціальних рівнянь з імпульсним ефектом. Побудовано узагальнену матрицю Гріна.